古代叙事文学中的私奔与殉情 ：以《司马相如列传》和《孔雀东南飞》为探讨中心 = Elopement and commit suicide for love in ancient narrative literature : focus on “Biography of Sima Xiangru” and “Peacock Flying Southeast” - 李静仪 Lee, Ching Yee (2018)
《史记·司马相如列传》和《孔雀东南飞》是中国汉代文学的经典，其迷人之处在于它们将美好的爱情与现实结合在一起，男女在追求真爱的同时，通过描写 双方家庭在婚姻中扮演了怎样的角色，反映出当时的礼教社会及婚姻制度的弊端。不管是司马相如和卓文君选择私奔，抑或是焦仲卿和刘兰芝选择殉情，都是无可奈 何下做出的决定。 将私奔与殉情对比，二者的结局固然是最显著的差异。然而，在他们各自做出选择之前，内心的挣扎与考量，以及下定决心的那一刹那，在微观的角度上都有 不同之处。因此，本文全面地分析这两个文本的人物刻画及情节发展，力求对这两个故事有更进一步的认识。从宏观的角度而言，笔者发现作为独特的文化社会现象，私奔与殉情也成为 影视剧集的题材，赞颂真爱的伟大能战胜一切。 “Biography of Sima Xiangru” and “Peacock Flying Southeast” are two classical works in Chinese literature during Han Dynasty. The fascinating part is they linked true love to reality. It was shown that while couple was trying to pursue true love, they should always take their families into consideration as they, especially their parents play important role in determining their love or even marriage. This proved that there were imperfections for marriage system in ritual society. Both Sima Xiangru who eloped with Zhuo Wenjun and Jiao Zhongqing who committed suicide together with Liu Lanzhi for love. They had no other choice but to make such painful decision. Comparing between elopement and commit suicide for love, the most significant difference was their story endings. However, they did struggle and consider a lot before making their decision respectively. From a micro view, there were differences between elopement and commit suicide for love, especially the moment they were determined and insisted on their decision were the only ways to go. Therefore, I will discuss the character image that were portrayed in the story, together with the story plot, to get a clearer picture of these two phenomena. From macro perspective, I discovered that both phenomena are related to society culture. Nowadays elopement and commit suicide for love have become major theme for drama and movies. It is evidence that the power of true love can eventually overcome everything.